329. Personalized dosimetric approach in advanced HCC patients treated with 90Y resin microspheres. (December 2018) - Cutaia, C.; Richetta, E.; Poli, M.; Pasquino, M.; Paradisi, B. Peiretti; Sacco, L.; Carbonatto, P.; Calvo, A.; Tabone, M.; Pellerito, R.E.; Stasi, M.
Abstract : Purpose: Radioembolization with 90 Y resin microspheres is becoming an effective therapeutic option for advanced HCC patients. Dosimetric methods are compared to standard ones to highlight the relevance of a personalized approach. Methods: The study was conducted on 42 HCC patients undergoing 90 Y resin-microspheres radioembolization. The optimal activity was calculated on pre-treatment 99m Tc-MAA CT-SPECT images with dosimetric approaches (Voxel and MIRD methods with the following dose treatment's goals: whole healthy liver (NL) <30–40 Gy and tumour (T) >120 Gy) and it was compared to the activity obtained with standard methods (BSA, fixed method). On 10 SPECT-CT images (IT_AC or IT_NOAC) the influence of CT attenuation correction was investigated: mean doses (T, NL) as well as DVH curves (D100, D95, D20, D2 ) were compared (using t-test). Results: 77% of patients received a mean administered activity (1.42 ± 0.52, range 0.70 ÷ 2.63 GBq) lower than the BSA activity (up to −1.3 GBq) and only in 23% of cases the activity was higher (+0.8 GBq). Similar results with bigger discrepancies were observed comparing the activity calculated with dosimetric and fixed method: 84% of patients received a lower activity than the one suggested by the fixed method (up to −1.7 GBq), 16% were administered with higher activity (up to 0.8 GBq). If the doses to NL were rescaled to BSA and fixed activity values, they would be significantly higher, exceeding the 30 Gy constraint in 54.2% of patients (BSA) and 70.8% (fixed). Mean T doses were 172 ± 145 Gy (IT_AC) and 181 ± 168 Gy (IT_NOAC) and mean scintigraphic NL doses 38 ± 23 Gy (IT_AC) and 30 ± 12 Gy (IT_NOAC) without statistical differences as well as in DVHs comparisons. NL IT_NOAC DVH points were in mean lower than IT_AC while higher discrepancies between the reconstructions were found in doses calculated to tumours. The results are shown in Fig. 1. Conclusions: A dosimetric approach is mandatory in 90 Y radioembolization because it is required by EU 2013/59 Directive but also to avoid under or over treatments; an accurate dosimetry can also be achieved on SPECT images without CT correction, which is useful, however, for volumes definition.